Multi-Purpose Structure-Integrated Zinc-Polyiodide Hybrid Flow Battery As Sustainable Energy Storage System for Extraterrestrial Environments - Girschik, Jan; Selle, Milan; Gläßer, Markus; Burfeind, Jens; Grevé, Anna (Meeting abstracts (Electrochemical Society), 2023)
For the energy supply of spacecrafts, such as space stations, satellites or orbiters, primarily solar power is used, which conversion, however, is subject to constant fluctuations due to rotational and orbital movements. In order to secure energy security for technical operations, the maintenance of scientific test series as well as life-support measures even during dark phases, various types of batteries such as nickel-hydrogen or nickel-cadmium batteries have been used as buffer storage over the years. However, due to the isolated locations in which they are used, energy storage systems for space applications must have a particularly long service life and operational reliability in order to be able to reduce resource-intensive replacement missions as well as hazards to people and technology. Since the battery systems used in space applications have in some cases shown significant deficits in these areas, a novel storage concept was developed in the "SpaceFlow" project, which was awarded third place in the europewide idea competition INNOspace Masters DLR Challenge, using the particularly safe and durable flow battery technology. The energy storage concept is based on the space-efficient integration of pressure-stable yet flexible flow battery cells into the supporting structure of spacecraft. In this way, in addition to energy storage as the primary task, other functions such as mechanical stiffening of the modules, support of thermal management or absorption of radiation can be realized. The "SpaceFlow"battery is realized as a zinc-polyiodide hybrid flow battery, which achieved incomparably high energy densities in laboratory tests. An energy density of 167 Wh/l was demonstrated and the potential to increase the energy density even up to 350 Wh/l was shown. The currently most widely used all-vanadium flow battery achieves energy densities of about 30 Wh/l. To optimize the cell chemistry zinc-polyiodide, various additives will be tested in the project. For a controlled formation of dendrites, for example, polyethylene glycol, methanesulfonic acid, chromium ions and, in general, alcohols, especially ethanol, could be added to the electrolytes as additives. In organic compounds, the presence of hydroxyl groups is an important factor in stabilizing the Zn ions. The deposition is also influenced by these. The search for additional alcohol and ether compounds offers the potential to find new additives. Chromium ions provide electrostatic shielding during zinc deposition, inhibiting dendrite growth. The iodine side (cathode) can be optimized mainly by improving the solubility of I2 in water. Stabilization of I2 without the binding of I- provides more free I-, which can react and help increase the capacity of the battery. Bromine ions or polyvinylpyrrolidone can be used to stabilize I2. Other additives such as KI and NH4Cl can be used for improved conductivity. Another approach is to improve diffusion at the cathode. For this purpose, a molybdenum sulfide coating can be applied, which improves the reaction rate with only a slight overpotential. The talk will present the novel storage concept and achievable functionalities as well as the latest project results of the flow cell design development and the design of a zinc polyiodide electrolyte, which must not be hazardous to humans and and at the same time must have a high energy density, to meet the requirements of space applications.